Forecasting base metal prices with the Chilean exchange rate. (August 2019) - Pincheira Brown, Pablo; Hardy, Nicolás
Abstract: In this paper we show that the Chilean exchange rate has the ability to predict the returns of the London Metal Exchange Index and of the six primary non-ferrous metals that are part of the index: aluminum, copper, lead, nickel, tin and zinc. The economic relationship hinges on the present-value theory for exchange rates, a floating exchange rate regime and the fact that copper represents about a half of Chilean exports and nearly 45% of Foreign Direct Investment. Consequently, the Chilean peso is heavily affected by fluctuations in the copper price. As all six base metal prices show an important comovement, we test whether the relationship between copper prices and Chilean exchange rates also holds true when it comes to the six primary non-ferrous metals. We find interesting evidence of predictability both in-sample and out-of-sample with traditional statistical measures. We also show that the information contained in the Chilean peso can successfully be used to obtain positive returns when trading base metals. Our paper is part of a growing literature that in the recent years has evaluated the ability of commodity currencies to forecast commodity prices. Highlights: We show that the Chilean exchange rate has the ability to predict the returns of the London Metal Exchange Index and of the six primary non-ferrous metals that are part of the index: aluminum, copper, lead, nickel, tin and zinc. We find sound evidence of predictability both in-sample and out-of-sample. The theoretical underpinnings of our findings rely on the present-value theory for exchange rate determination and on the importance of copper on Chile's trade balance. We consider both monthly and quarterly databases. Stronger predictability emerges from the latter. Out-of-sample R² tends to be modest, with an average of 2.7% and 9.7% with monthly and quarterly data respectively.